The Effects of Catechin, Lipoic Acid, Resveratrol and Potassium Bromate on Fatty Acid, Lipophylic Vitamins and Cholesterol Levels in Muscle of Wistar Rats - Keser, Serhat; Yilmaz, Okkes; Tuzcu, Mehmet; Erman, Orhan; Irtegun, Sevgi (Chem Soc Pakistan, 2012)
The aim of this study was to examine the effects of potassium bromate, catechin, lipoic acid and resveratrol on the level of fatty acids, lipophylic vitamins and cholesterol in muscle of Wistar rats. In this study, Wistar rats were randomly divided into five groups: I. Control (C), 2. KBrO3 (K), 3. Catechin+KBrO3 (Cat), 4. Lipoic Acid+KBrO3 (LA) and 5. Resveratrol+KBrO3 (R). Whereas, lipophylic vitamins and cholesterol were measured by HPLC, in muscle, fatty acid levels were measured by gas chromatography. In the present study, alpha-tocopherol level was significantly increased in the R group, but its level was not different between the C group and the other groups. Cholesterol level was decreased in the R group, but its level was not different between C group and the other groups. The stearic acid (18:0) and arachidonic acid (20:4) levels were increased in all groups when compared to the C group. Our results confirm that resveratrol and KBrO3 can be affected the amount of important fatty acids which substrates in fatty acids metabolism and resveratrol reduced the cholesterol level of muscle of Wistar rats.
Keywords: Stearoyl-Coa Desaturase; Low-Density-Lipoprotein; Arachidonic-Acid; Lipid-Peroxidation; Mesangial Cells; Metabolism; Antioxidant; Phospholipase-A2; Erythrocytes; Calcium